Active Portfolio Management: A Quantitative Approach to Providing Superior Returns and Controlling Risk - Connor, Gregory (Review of Financial Studies, 2000)
This unusual book is not intended chiefly as a textbook for investment courses. The book's principal target audience is quantitatively inclined investment management professionals with some masters-level knowledge of finance. However, it could make an excellent textbook for a second-year MBA course in quantitative portfolio management; the authors mention this as a possible use of the book. Be warned: anyone teaching a course based on this book would need to make a substantial commitment to mastering and expositing a large body of unfamiliar, analytical material. The payoff would be a class full of students who could not complain that the course was not practically relevant. Alternatively, the book could play a valuable supporting role in an investments course as optional outside reading. Many M.B.A. students query the usefulness of modern portfolio theory in business applications. In this book the authors nearly describe how to build a fully functional investment management business, and it is all done on a foundation of modern portfolio theory.